Malaysian Insurance Law - Cheah, You Sum; Ruzian Markom; Hasani Mohd Ali (Thomson Reuters Asia, 2023)
The Second Edition of Malaysian Insurance Law offers a comprehensive exploration of the intricate realm of insurance law in Malaysia, providing invaluable insights into its principles, practical aspects, legal framework, and regulations. Building on the success of the First Edition published in 2018, which quickly became the go-to reference for Malaysian practitioners, students, regulators, supervisory authorities, and insurance industry professionals, this updated edition continues to cater to the essential knowledge required in insurance law. This text delves into the historical context of insurance practices and the sources of insurance law in Malaysia. It extensively discusses fundamental principles and concepts central to insurance law, such as insurable interest, the formation of insurance contracts, warranties in insurance contracts, and the doctrines of misrepresentation and non-disclosure in insurance and takaful contracts. Additionally, the book explores key topics including the principle of indemnity, subrogation and contribution, the doctrine of proximate cause in insurance, claims processes, agents and brokers, as well as the legal and regulatory framework governing insurance practices in Malaysia. In this updated Second Edition, the text emphasizes significant cases that have emerged since the release of the First Edition, particularly focusing on areas related to the principle of insurable interest and utmost good faith. The content has been meticulously reviewed and revised by two new authors, both distinguished legal scholars and insurance law researchers. Furthermore, this edition introduces two additional chapters that cover the intermediaries of insurance business and the regulation of insurance entities. Malaysian Insurance Law, Second Edition, serves as an up-to-date and indispensable resource for insurance practitioners, legal professionals, academics, students, and anyone keen on comprehending the complexities of the insurance industry in Malaysia.